Pengaruh Desentralisasi Fiskal dan Pertumbuhan Ekonomi terhadap Ketimpangan Antar Daerah - Latifah; Rahayu, Dewi (PPJP ULM, 2019)
This research was conducted to determine the effect of fiscal decentralizationand economic growth of South Kalimantan Province on inter-regional inequality. Thedata used in this study is secondary data with 12 years (time series), which ispublished once a year by the Central Statistics Agency of the Province of SouthKalimantan. The data needed is data on total balancing funds, economic growth, andGDP at the current price and population. The data analysis technique used is themultiple linear regression analysis methods.The results showed that simultaneously and partially, the variables of fiscal decentralization and economic growth had a positive and significant effect on inter-regional inequality.